Avaliação do efeito hipoglicemiante e hipocolesterolêmico do polvilho da fruta-de-lobo (Solanum lycocarpum St. Hil) - Rocha, Denise Alvarenga (2009)
This work was conducted with the purpose of evaluating the hypoglycemia provoking and hypocholesterolemic effect of flour of fruit-of-wolf in rats. This is a herbal medicine extracted from the unripe lobo fruit (Solanum lycocarpum St. Hil) according to the folk knowledge. Little is known about this flour, but is marketed in drugstores pharmacies in the region of Lavras, in the form if 300mg capsules. It is utilized in the treatment of diabetes mellitus, and other therapeutic effects are ascribed to it, such as reduction of obesity and cholesterol, but without any scientific knowledge. To prepare the sample, eighty fruit-of-wolf were collected in the pasture areas of the Animal Science Department of the UFLA/Lavras-MG. 61 fruits were selected, taken into consideration the size and maturation stage and from these fruits, the starch was obtained through a particular technique. In this one, moisture, proteins, ether extract, ashes, food fibers and carbohydrates were analyzed. In the animals which were utilized in the experiment of the hipoglicemiante evaluation, diabetes mellitus was induced by utilizing streptozotocin 40 mg/kg by endovenous via. glycemia was evaluated weekly, in addition to the parameters: animals weight, food intake, diuresis and water intake. Histological slides were done at the end of the experiment to verify lesions in the liver and pancreas. Fruit-of-wolf flour reduced glycemia by around 20% in the treated diabetic rats, showing that that herbal medicine has an efficacy as a hypoglycemia-provoker in rats. The experimental animals utilized in the evaluation of the hypocholesterolemic effect were fed a commercial diet enriched with cholesterol and cholic acid. In these, the following analyses were performed: total cholesterol total serum cholesterol, HDL-cholesterol, total hepatic cholesterol, total hepatic lipids and with the liver, light microscopy slides for evaluating the hepathocytes were done. Also, body weight and feed consumption of these animals were evaluated. In that experiment, fruit-of-wolf flour did not influence the levels of serum cholesterol, but it reduced the levels of hepatic cholesterol and ratio VLDL+LDL/HDL.